2015
DOI: 10.1093/ntr/ntv108
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Fagerström Test for Cigarette Dependence and Cigarette Dependence Scale in a Treatment-Seeking Sample of Pregnant Smokers

Abstract: Known previously as the Fagerström Tolerance Questionnaire 2 and Fagerström Test for Nicotine Dependence 3,4 the six-item FTCD is the most widely-used, brief measure of cigarette dependence. 5 The five-item Cigarette Dependence Scale 6 is also a brief and valid measure of cigarette dependence. The CDS-5 has psychometric properties similar to its parent measure, the CDS-12, but with less comprehensive content in terms of tapping compulsion, withdrawal symptoms, loss of control, time allocation, neglect of othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
(68 reference statements)
1
8
0
2
Order By: Relevance
“…More robust outcome predictors are needed as, so far, few self-report measures have proven to be reliable. For example, even self-reported nicotine dependence severity shows inconsistent predictive value (Berlin et al, 2016; McPherson et al, 2014), and recent work in the same subject sample examined in the present manuscript found that a variety of predictors previously identified (mood, impulsiveness, age) were not predictive of treatment outcome (Wilcox et al, 2017). …”
Section: Introductionmentioning
confidence: 48%
“…More robust outcome predictors are needed as, so far, few self-report measures have proven to be reliable. For example, even self-reported nicotine dependence severity shows inconsistent predictive value (Berlin et al, 2016; McPherson et al, 2014), and recent work in the same subject sample examined in the present manuscript found that a variety of predictors previously identified (mood, impulsiveness, age) were not predictive of treatment outcome (Wilcox et al, 2017). …”
Section: Introductionmentioning
confidence: 48%
“…Of the 40 observational studies, 19 were cross‐sectional and 21 were cohort studies . Fifteen studies used secondary data from RCTs .…”
Section: Resultsmentioning
confidence: 99%
“…All the studies recruited participants who were at least 16 years of age and the mean age of the women ranged from 16 to 50 years. Of the 17 studies (31.5%) that reported quit attempts, all or most of the participants made a quit attempt in 15 studies , while two other studies reported quit attempts for only 17% and 30% of the participants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, among pregnant smokers the odds of cessation have been related inversely to baseline cotinine level 24, and in another study 29 scores for Fagerström Test of Cigarette Dependence (FTCD), urges to smoke and withdrawal symptoms failed to predict smoking status 2 weeks following the quit date. Therefore, in this study we examined the predictive validity of common measures of dependence on smoking cessation in pregnancy.…”
Section: Introductionmentioning
confidence: 99%